Clinical management and outcomes of primary ovarian leiomyosarcoma - Experience from a sarcoma specialist unit - Elena Cojocaru; Githmi Palahepitiva Gamage; John Butler; Desmond P. Barton; Khin Thway; Cyril Fisher; Christina Messiou; Aisha B. Miah; Shane Zaidi; Spyridon Gennatas; Charlotte Benson; Paul Huang; et al. (Elsevier, 2021)
Ovarian sarcomas account for 1% of all ovarian malignancies and amongst these, primary ovarian leiomyosarcoma is the rarest subtype. Primary ovarian leiomyosarcoma has a very poor prognosis, with less than 20% of patients being alive at 5 years. Only a few cases have been published in the literature and there is very limited knowledge on the clinical behaviour and optimal management of these tumours. We have performed a retrospective analysis of a prospectively maintained database to identify all primary ovarian leiomyosarcoma diagnosed and treated at the Royal Marsden NHS Foundation Trust between 1998 and 2020. Sixteen patients were identified from our database and fifteen were eligible for the analysis. Twelve patients presented with localized disease and underwent initial surgery and three patients had metastatic disease at presentation. Recurrence-free survival post-surgery was 16 months. Eight patients received first-line chemotherapy and four patients received second-line chemotherapy. Two patients had indolent metastatic disease and benefited from local therapies only. The median overall survival in the metastatic setting in our cohort was 51 months, which is consistent with previously published cases. Primary ovarian leiomyosarcoma is an extremely rare malignancy with a poor prognosis. This study is the largest case series of primary ovarian leiomyosarcoma published to date, providing clinically important information regarding survival and metastatic rate as well as treatment outcomes in the metastatic setting.